The prognostic role of p-53 protein Immunohistochemical expression in multiple myeloma - Muna A. Abdullah; Abdulkareem M. Jaafar; Adel R. ALsaadawi (مجلة كلية الطب, 2015)
Background: Several factors render multiple myeloma (MM) an interesting subject for study by researchers. These include marked progress in understanding the molecular biology of normal and neoplastic plasma cells and recent advances in molecular genetics techniques. Among molecular markers, p-53 cancer suppressor gene have been widely studied. Aim: is to correlate p-53 protein expression in multiple myeloma, as examined by immunohistochemical method, with some pathological and clinical parameters (Clinical stage and cytological grade). Patients and methods: This is a retrospective study; whereby archival paraffin-embedded BM tissue blocks along with the clinical and hematological records of fifty patients (29 males and 21 females), with multiple myeloma and twenty controls were obtained from the Department of Hematology of the Medical City Teaching Laboratories in the period from April 2012 to April 2014. P-53 was studied by immunohistochemical staining. Results: There was a significant positive linear correlation between increasing scores of p-53 and advancing clinical stages of disease. There was a significant positive linear correlation between increasing scores of p-53 and decreasing maturity of plasma cells. Conclusions: Multiple myeloma patients with advanced clinical stages and immature plasma cell morphology had high p-53 scores. Since the above-mentioned factors are known independent prognostic factors, p-53 expression can readily be adopted to identify myeloma patients with an adverse prognosis.